2016
DOI: 10.1007/s12272-016-0847-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of biomimetic shear stress on cellular uptake and mechanism of polystyrene nanoparticles in various cancer cell lines

Abstract: Cancer cells in the tumor microenvironment are affected by fluid shear stress generated by blood flow in the vascular microenvironment and interstitial flows in the tumor microenvironment. Thus, we investigated how fluidic shear stress affects cellular uptake as well as the endocytosis mechanism of nanoparticles using a biomimetic microfluidic system that mimics the human dynamic environment. Positively charged amino-modified polystyrene nanoparticles (PSNs) at 100 μg/mL were delivered to cancer cells under st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…However, the transport of Lucifer yellow increases slightly perhaps due to the shear stress effect. Indeed, it has previously been reported that shear stress increases the endocytosis of small molecules [12]. The results suggest that although Lucifer yellow is typically used as a marker for paracellular transport, the applied shear stress may induce the A549 cells to uptake Lucifer yellow and transport it across the cell monolayer via the transcellular route.…”
Section: B Microfluidic Device Resultsmentioning
confidence: 77%
“…However, the transport of Lucifer yellow increases slightly perhaps due to the shear stress effect. Indeed, it has previously been reported that shear stress increases the endocytosis of small molecules [12]. The results suggest that although Lucifer yellow is typically used as a marker for paracellular transport, the applied shear stress may induce the A549 cells to uptake Lucifer yellow and transport it across the cell monolayer via the transcellular route.…”
Section: B Microfluidic Device Resultsmentioning
confidence: 77%
“…Here, we observed a significant change in effective shear stress as the cell transitions from undrained to drained condition. It is essential to study the effect of external stimulus on cells as they are often subjected to fluid shear stress generated by the blood flow in the vascular microenvironment and interstitial flows in the tumor microenvironment [64]. In one of the studies using biomimetic microfluidic system, it was shown that the uptake of polystyrene nanoparticles in biomimetic dynamic conditions (cells are under higher shear stress than static system) by cancer cells was higher than that in a static system [64].…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to study the effect of external stimulus on cells as they are often subjected to fluid shear stress generated by the blood flow in the vascular microenvironment and interstitial flows in the tumor microenvironment [64]. In one of the studies using biomimetic microfluidic system, it was shown that the uptake of polystyrene nanoparticles in biomimetic dynamic conditions (cells are under higher shear stress than static system) by cancer cells was higher than that in a static system [64]. Similar study has been performed in different cell lines such as Human Embryonic Kidney (HEK) 293T cells, Panc1 cells, human lung adenocarcinoma (A549) cells and human colorectal adenocarcinoma (HT29) cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that fluid shear stress could prompt ovarian cancer cell dissemination, enrich cancer stem cell population as well as enhance tumor's chemoresistance to anti-cancer drugs. Almost all current microfluidic devices incorporating fluid flow can generate a shear stress with physiologically relevant value and can demonstrate the impact of shear stress in cultured tumor cells in vitro [157][158][159][160]. In current microfluidic models culturing three-dimensional tumors, fluid only flows around tumor spheroids and the quantified shear stress value is the shear stress on the outer surface of the tumor.…”
Section: Shear Stressmentioning
confidence: 99%